2021
DOI: 10.1144/sp509-2019-126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and origin of large Campanian depressions within the Chalk Group of the Danish Central Graben – implications for hydrocarbon exploration and development

Abstract: This study re-examines large and deep U-shape reflections (2-4 km wide, 100-200 m deep) within the Upper Cretaceous-Danian Chalk Group in the inverted Roar Basin of in the Danish North Sea, previously interpreted as a moat associated with a contour-parallel current system and/or erosive channels by gravity-driven turbidites. Improved 3D seismic data quality and seismic interpretation techniques helped to identify overlooked reflection terminations that suggest that rather than a linear depression, the U-shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…The significance of the burial model for the North Sea Basin is fourfold: (1) the current porosity bipartition was established in the end of the Oligocene to Middle Miocene, during which several source rocks could expel biogenic gas or thermogenic hydrocarbons (Kubala et al, 2003; Smit et al, 2021); (2) it predicts the occurrence of a palaeo‐lithification front within the Chalk Group in the overpressured North Sea Basin and not an ongoing mechanical/chemical compaction of the chalk as proposed by Japsen et al (2011); (3) The prediction of a regional lithification front is of importance for building velocity models and depth‐conversion of seismic data for areas with more sparse datasets (such as nearshore and onshore Denmark). Lastly, it shows an integrative workflow that may be applied in other overpressured basins for other lithologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of the burial model for the North Sea Basin is fourfold: (1) the current porosity bipartition was established in the end of the Oligocene to Middle Miocene, during which several source rocks could expel biogenic gas or thermogenic hydrocarbons (Kubala et al, 2003; Smit et al, 2021); (2) it predicts the occurrence of a palaeo‐lithification front within the Chalk Group in the overpressured North Sea Basin and not an ongoing mechanical/chemical compaction of the chalk as proposed by Japsen et al (2011); (3) The prediction of a regional lithification front is of importance for building velocity models and depth‐conversion of seismic data for areas with more sparse datasets (such as nearshore and onshore Denmark). Lastly, it shows an integrative workflow that may be applied in other overpressured basins for other lithologies.…”
Section: Discussionmentioning
confidence: 99%
“…First, the burial model suggests that the bipartition of the Chalk Group was established as several source rocks entered the hydrocarbon generation window and thus source, reservoir and seal were in place (Smit et al, 2021). The occurrence of low‐porous (0%–10%) chalk below RPM acted as a seal underneath the reservoir in the upper part of the Chalk Group, and structural deformation of this lower seal must have been critical to create fluid flow pathways since fracture permeability is several orders of magnitude higher than matrix permeability (especially for low‐porosity chalks; Caine et al, 1996; Sagi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). The HARPs were therefore interpreted to indicate MDAC beds, and stable carbon isotope (δ 13 C) values of -40 ‰ to -20 ‰ for these carbonates were interpreted to suggest a mainly thermogenic origin for the methane (Smit et al, 2021). However, Burns (1998) showed that MDACs with δ 13 C values of -40 ‰ were sourced from biogenic gas, and therefore some mix with biogenic gas cannot be ruled out.…”
Section: Good To High Seal Integritymentioning
confidence: 99%
“…2). In both the Rogaland and Hordaland Groups, carbonate stringers have been identified in many intervals in well reports and logs and are interpreted as MDACs, for which the source of methane may have been biogenic, thermogenic or a mixture of the two (Smit et al, 2021). The overburden is constituted by the Nordland Group comprising middle Miocene -Pliocene marine mudstones with subordinate silts and fine sands.…”
Section: Stratigraphymentioning
confidence: 99%